Can Pokémon GO catch brands? The fit effect of game characters and brands on efficacy of brand communications. Issue 6 (18th August 2019) - Kim, Dong Hoo; Kim, Seoyeon; Song, Doori
Abstract: Given the recent popularity of augmented reality (AR) games, such as Pokémon GO, this study explores the congruence effect of game characters and brands on brand evaluations and the underlying mechanisms of the effect. Prior gaming experience and motivations are taken into account. An experiment reveals that inexperienced gamers are likely to have more favorable evaluations of the target brands when the images of game characters match the brand images, whereas these effects disappear for experienced gamers. Furthermore, the research demonstrates that experienced gamers are more likely to hold game-specific motivations than the inexperienced, while inexperienced gamers are motivated more by social interaction for playing AR games. Lastly, a mediation analysis reveals that social interaction-related motivation mediates inexperienced gamers' preference of character–brand congruence. This study sheds light upon how AR games can be utilized by brand communicators.